Phytoplankton variability and community structure in relation to hydrographic features in the NE Aegean frontal area (NE Mediterranean Sea). (1st October 2017) - Lagaria, A.; Mandalakis, M.; Mara, P.; Frangoulis, C.; Karatsolis, B.-Th.; Pitta, P.; Triantaphyllou, M.; Tsiola, A.; Psarra, S.
Abstract: The structure of phytoplankton community in the salinity-stratified Northeastern Aegean frontal area adjacent to the Dardanelles Straits was investigated on a seasonal basis (autumn, spring and summer) and in relation to circulating water masses: the modified Black Sea Water (BSW) and the Levantine Water (LW). By employing High Performance Liquid Chromatography (HPLC) for the analysis of phytoplankton pigments in conjunction with conventional cell counting methodologies (i.e. inverted light microscopy, flow cytometry) and primary production measurements, a comprehensive qualitative and quantitative characterization of phytoplankton community composition and its activity was conducted. Chlorophyll- a normalized production and estimated growth rates presented the highest values within the 'fresh' BSW mass during summer, though generally growth rates were low (<0.4 d −1 ) at all seasons. The spatiotemporal variation of BSW outflow was found to greatly affect the relative contribution of pico-, nano- and micro-phytoplankton to total phytoplankton biomass and production. Large cell organisms, and in particular diatoms, were closely associated with the surface BSW masses outflowing from the Straits. Our results showed that all phytoplankton size components were significant over time and space suggesting a rather multivorous food web functioning of the system. Highlights: NE Aegean Sea is characterized by the presence of Black Sea Water (BSW) mass. The spatiotemporal variation of BSW outflow affected phytoplankton structure. Diatoms were closely associated with the surface BSW mass. Phytoplankton structure changes elucidated relevant variations of production rates. NE Aegean Sea presented a rather multivorous food web functioning.